Generation of a Spiral Ganglion Neuron Degeneration Mouse Model - Hu, Zhengqing; Komal, Fnu; Singh, Aditi; Deng, Meng (Frontiers in Cell and Developmental Biology, 2021)
Spiral ganglion neurons (SGNs) can be injured by a wide variety of insults. However, there still is a lack of degeneration models to specifically damage the SGNs without disturbing other types of cells in the inner ear. This study aims to generate an SGN-specific damage model using the Cre-LoxP transgenic mouse strains. The Cre-inducible diphtheria toxin receptor (iDTR +/+) knock-in mouse strain was crossed with a mouse strain with Cre activity specific to neurons (NeflCreER/CreER). Expression of the Cre-recombinase activity was evaluated using a reporter mouse strain Ai9 at pre-hearing, hearing onset, and post-hearing stages. Accordingly, heterozygous NeflCreER/+;iDTR+/- mice were treated with tamoxifen at postnatal day 1-5 (P1-5), followed by diphtheria toxin (DT) or vehicle injection at P7, 14, and 21 to study for the SGN loss. Robust tamoxifen-induced Cre-mediated Ai9 tdTomato fluorescence was observed in the SGN area of the heterozygous NeflCreER/+;Ai9+/- mouse treated with tamoxifen, whereas vehicle-treated heterozygote did not show tdTomato fluorescence. Compared to vehicle-treated NeflCreER/+;Ai9+/- mouse, DT-treated NeflCreER/+;Ai9+/- mouse showed significant auditory brainstem response threshold shifts and SGN cell loss. Hair cell count and functional study did not show significant changes. These results demonstrate that the NeflCreER/CreER mouse exhibits inducible SGN-specific Cre activity in the inner ear, which may serve as a valuable SGN damage model for the inner ear regeneration research.